Bioprosthetic Valve Thrombosis: Insights from Transcatheter and Surgical Implants. Issue 5 (2nd September 2020) - Dangas, George; Chiarito, Mauro; O'Gara, Patrick; Makkar, Raj; Gurbel, Paul; Leipsic, Jonathon; Batchelor, Wayne; Holmes, David R.; Poppas, Athena; Carroll, John; Kapadia, Samir; Mack, Michael; et al.
ABSTRACT: Although aortic valve replacement with implantation of a bioprosthesis has been widely performed for more than 50 years, appreciation of the development of bioprosthetic leaflet thrombosis has increased recently with the emergence of transcatheter aortic valve replacement (TAVR) and the use of advanced imaging modalities, such as 4-dimensional computed tomographic angiography. Recent observational and randomized studies have demonstrated how this condition could affect patients treated with either TAVR or surgical aortic valve replacement (SAVR). The clinical relevance of bioprosthetic valve thrombosis and the optimal antithrombotic strategies to prevent this condition in patients treated with SAVR or TAVR are still a matter of debate, while anticoagulation is considered effective treatment to address bioprosthetic valve thrombosis once it is diagnosed. This review provides an overview on timing and mechanism of bioprosthetic valve thrombosis, its prevalence and clinical impact in patients treated with TAVR or SAVR, and how the different designs of various types of bioprostheses could influence the risk of thrombosis.